Sudden cardiac death in COVID-19 patients, a report of three cases - Shirazi, Samira (Future Cardiol, 2020)
The mortality rate of coronavirus disease-19 (COVID-19) has been reported as 1–6% in most studies. The cause of most deaths has been acute pneumonia. Nevertheless, it has been noted that cardiovascular failure can also lead to death. Three COVID-19 patients were diagnosed based on reverse transcriptase-polymerase chain reaction of a nasopharyngeal swab test and radiological examinations in our hospital. The patients received medications at the discretion of the treating physician. In this case series, chest computed tomography scans and electrocardiograms, along with other diagnostic tests were used to evaluate these individuals. Sudden cardiac death in COVID-19 patients is not common, but it is a major concern. So, it is recommended to monitor cardiac condition in selected patients with COVID-19.